Nitrate or ammonium: Influences of nitrogen source on the physiology of a green alga. Issue 3 (10th January 2019) - Lachmann, Sabrina C.; Mettler‐Altmann, Tabea; Wacker, Alexander; Spijkerman, Elly
Abstract: In freshwaters, algal species are exposed to different inorganic nitrogen (Ni ) sources whose incorporation varies in biochemical energy demand. We hypothesized that due to the lesser energy requirement of ammonium ( NH 4 + )‐use, in contrast to nitrate ( NO 3 - )‐use, more energy remains for other metabolic processes, especially under CO2 ‐ and phosphorus (Pi ) limiting conditions. Therefore, we tested differences in cell characteristics of the green alga Chlamydomonas acidophila grown on NH 4 + or NO 3 - under covariation of CO2 and Pi ‐supply in order to determine limitations, in a full‐factorial design. As expected, results revealed higher carbon fixation rates for NH 4 + ‐grown cells compared to growth with NO 3 - under low CO2 conditions. NO 3 - ‐grown cells accumulated more of the nine analyzed amino acids, especially under Pi ‐limited conditions, compared to cells provided with NH 4 + . This is probably due to a slower protein synthesis in cells provided with NO 3 - . In contrast to our expectations, compared to NH 4 + ‐grown cells NO 3 - ‐grown cells had higher photosynthetic efficiency under Pi ‐limitation. In conclusion, growth on the Ni ‐source NH 4 + did not result in a clearly enhanced Ci ‐assimilation, as it was highly dependent on Pi and CO2 conditions (replete or limited). Results are potentially connected to the fact that C. acidophila is able to use only CO2 as its inorganic carbon (Ci ) source. Abstract : Our study shows that N‐source affect Chlamydomonas acidophila differently than those algae which are in contrast not restricted to CO2 as a Ci ‐source. Pi supply resulted in a minor influence, and amino acid composition was clearly affected by N‐source with interesting covariance of CO2 and Pi .